Pengaruh Interaksi Sosial terhadap Kemampuan Emosi Anak Usia Dini di Raudhatul Athfal Tunas Kualuh Kecamatan Kualuh Hilir Kabupaten Labuhanbatu Utara - Daulay, Maulida Rahmah; Hasibuan, Humaidah Br.; Nasution, Raisah Armayanti (ALSYS, 2024)
This study aims to determine the effect of social interaction on the emotional abilities of early childhood in Raudhatul Athfal Tunas Kualuh, Kualuh Hilir District, North Labuhanbatu Regency and identify the effect of social interaction on children's emotional abilities. This type of research is descriptive quantitative research, the population in this study involved 30 respondents and respondents using instruments that were tested for validity and reliability of sampling techniques using probability techniques, data collection instruments using observation and documentation. As for the formulation of the problem, namely how is the social interaction of children in RA Tunas Kualuh, how is the emotional ability of children in RA Tunas Kualuh, and is there an influence of social interaction on children's emotional abilities in RA Tunas Kualuh? The data analysis techniques used are normality test, and homogeneity test and hypothesis test (T test). Based on the results of the study that the validity test shows that the instruments for social interaction variables (X1) and emotional abilities (Y2) are valid and reliable. Normality test with Kolmogorov-Smirnov shows that the data is normally distributed (Asymp.Sig. = 0.370). The homogeneity test showed that the variance between groups was homogeneous (Sig = 0.517). The results of the hypothesis test (T test) indicated that social interaction has a significant influence on children's emotional abilities (Sig = 0.000), with a Beta coefficient of -0.723. This study concluded that social interaction plays a significant role in influencing children's emotional abilities in RA Tunas Kualuh, with the instruments used being valid and reliable. Thus Ho is rejected and Ha is accepted that social interaction does have a significant influence on children's emotional abilities.